The Legal Politics of Modern Retail Arrangement Based on Pancasila Values in the Protection of the People's Market - Abdul Wahab; Yorman Yorman (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2026)
he purpose of this research is to formulate a legal policy of modern retail structuring that is oriented towards the value of Pancasila in protecting the people's market and maintaining the sustainability of the local economy in Central Lombok Regency. This study uses a socio-legal empirical research design by integrating normative legal analysis and spatial empirical approaches based on Geographic Information System (GIS) as well as qualitative interviews. The normative analysis is focused on Central Lombok Regency Regional Regulation Number 7 of 2021 concerning the Arrangement and Development of People's Markets, Shopping Centers, and Supermarkets. Meanwhile, empirical analysis was carried out through mapping 139 modern retail outlets, measuring distance to the people's market, field observations, and interviews with 24 informants consisting of market traders, local government officials, and modern retail managers. The results of the study show that the distribution of modern retail is concentrated in sub-districts with economic activity, such as Praya and Pujut. Of the 139 outlets, as many as 63 outlets are within a radius of less than 1 kilometer from the people's market, and some are very close, which causes asymmetrical competition between large capital and small traders. The implementation of the Regional Regulation is still formal administrative and does not reflect substantive protection of the people's market. The values of Pancasila, especially social justice and the people, have not been operationally internalized in the zoning, licensing, and supervision systems. This study concludes that the legal politics of modern retail arrangements need to be reoriented through the establishment of buffer zones to protect the people's market, the evaluation of permits based on socio-economic impacts, and the involvement of traders in the policy process so that the modern retail arrangement truly reflects the values of Pancasila and maintains the sustainability of the local economy.